2019
DOI: 10.2147/cmar.s215697
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antibiotic therapy augments the efficacy of gemcitabine-containing regimens for advanced cancer: a retrospective study</p>

Abstract: BackgroundThe addition of antibiotics reportedly augments the efficacy of gemcitabine (GEM) in tumor-bearing mice. However, whether this phenomenon is also observed in cancer patients remains unclear. In the present study, we aimed to assess whether antibiotics for treatment or prevention of infection augments treatment efficacies of GEM-containing regimens in patients with any type of cancer.MethodsMedical records of patients diagnosed with cancer histopathologically and treated with GEM-containing regimens (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…A previous study [7] revealed that a decrease in intratumor bacteria by antibiotic treatment augments the antitumor efficacy of gemcitabine in tumor-bearing mice. On the basis of that report [7], we retrospectively demonstrated that antibiotic treatment augments the treatment efficacy of gemcitabine-based therapy in advanced cancer patients [8]. In addition, a decrease in bacteria by adding antibiotics also augments the cytotoxicity of oxaliplatin but not of irinotecan in the CRC cell line in vitro [7], which is consistent with our results in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A previous study [7] revealed that a decrease in intratumor bacteria by antibiotic treatment augments the antitumor efficacy of gemcitabine in tumor-bearing mice. On the basis of that report [7], we retrospectively demonstrated that antibiotic treatment augments the treatment efficacy of gemcitabine-based therapy in advanced cancer patients [8]. In addition, a decrease in bacteria by adding antibiotics also augments the cytotoxicity of oxaliplatin but not of irinotecan in the CRC cell line in vitro [7], which is consistent with our results in this study.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study reported improvement in the treatment efficacy of anticancer agents by adding antibiotics in pancreatic cancer patients [8], indicating that this improvement is independent of the tumor primary site. In contrast, improvement in the treatment efficacy of anticancer agents by adding antibiotics seems to depend on the type of anticancer agent.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[ 11 ] Imai et al reported that the use of antibiotics during a gemcitabine-containing regimen for various cancers is associated with increased survival. [ 12 ] However, little is known about whether the use of antibiotics leads to a better clinical outcome of GnP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] In clinical settings, a few monocenter retrospective studies have reported the association between the use of antibiotics before or during chemotherapy and clinical outcomes of gemcitabine monotherapy [ 11 ] and combination therapy. [ 12 ] However, little is known about the association between the use of antibiotics and efficacy of GnP combination therapy, which is regarded as the standard therapy for advanced pancreatic cancer. Therefore, we conducted a retrospective study to elucidate the association between the use of antibiotics and efficacy of GnP.…”
Section: Introductionmentioning
confidence: 99%